First results from the TNG50 simulation: the evolution of stellar and gaseous discs across cosmic time. Issue 3 (9th September 2019) - Pillepich, Annalisa; Nelson, Dylan; Springel, Volker; Pakmor, Rüdiger; Torrey, Paul; Weinberger, Rainer; Vogelsberger, Mark; Marinacci, Federico; Genel, Shy; van der Wel, Arjen; Hernquist, Lars
Abstract: We present a new cosmological, magnetohydrodynamical simulation for galaxy formation: TNG50, the third and final instalment of the IllustrisTNG project. TNG50 evolves 2 × 2160 3 dark matter particles and gas cells in a volume 50 comoving Mpc across. It hence reaches a numerical resolution typical of zoom-in simulations, with a baryonic element mass of $8.5× 10^4\, {\rm M}_{\odot }$ and an average cell size of 70–140 pc in the star-forming regions of galaxies. Simultaneously, TNG50 samples ∼700 (6500) galaxies with stellar masses above $10^{10} \, (10^8)\, {\rm M}_{\odot }$ at $z$ = 1. Here we investigate the structural and kinematical evolution of star-forming galaxies across cosmic time (0 ≲ $z$ ≲ 6). We quantify their sizes, disc heights, 3D shapes, and degree of rotational versus dispersion-supported motions as traced by rest-frame V -band light (i.e. roughly stellar mass) and by $\rm H\, α$ light (i.e. star-forming and dense gas). The unprecedented resolution of TNG50 enables us to model galaxies with sub-kpc half-light radii and with ≲300-pc disc heights. Coupled with the large-volume statistics, we characterize a diverse, redshift- and mass-dependent structural and kinematical morphological mix of galaxies all the way to early epochs. Our model predicts that for star-forming galaxies the fraction of disc-like morphologies, based on 3D stellar shapes, increases with both cosmic time and galaxy stellar mass. Gas kinematics reveal that the vast majority of $10^{9-11.5}\, {\rm M}_{\odot }$ star-forming galaxies are rotationally supported discs for most cosmic epochs ( V rot /σ > 2–3, $z$ ≲ 5), being dynamically hotter at earlier epochs ($z$ ≳ 1.5). Despite large velocity dispersion at high redshift, cold and dense gas in galaxies predominantly arranges in disky or elongated shapes at all times and masses; these gaseous components exhibit rotationally dominated motions far exceeding the collisionless stellar bodies.